Santiago de las Atalayas, ¿sepultura de forasteros? Pleito entre sus vecinos por el traslado de la ciudad, 1780-1799 (2019)
ABSTRACT: This article analyzes the transfer of the city of Santiago de las Atalayas in 1780, analyzing the city ideals of the time and the diverse environmental and physical conditions expressed by those in favor or against this determination. The article explores how a community understood the city and the diverse strategies to procure its sustainability and durability. The transfer of an urban center generates questions about the factors that contributed to the sustainability or permanence of cities and why they were accepted or rejected when their preservation was sought.